(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the effect of three different incubation times on in vitro maturation of domestic cat oocytes. Thus, ovaries (n = 42) were submitted to slicing procedure and the oocytes recovered were classified; only good quality oocytes (Grade I and II) underwent in vitro maturation for three different periods (24 vs. 30 vs. 36 h) in supplemented TCM-99 medium. After, oocytes were evaluated for cumulus cell expansion and presence of the first polar body. After six replicates (7 ± 1,7 ovaries per replicate), a total of 334 viable oocytes were recovered. Differences (p <0.05) were observed regarding the percentage of oocytes presenting expansion of the cumulus cells, where higher values were observed in the group of oocytes incubated for 36 h (84.3%), when compared to 30 (73.4%) and 24 h (71.0%). Moreover, differences were also observed regarding the presence of the first polar body (24 h: 29.7%; 30 h: 58.2%; 36 h: 69.8%). We conclude that the incubation period influenced the maturation rates, indicating 36 h as the ideal period for the in vitro maturation of domestic cat oocytes in supplemented TCM-199 medium.